Code Switching and Code Mixing in Youtube’s “Bule KW” Channel - Hafsoh Armiya; Christina Damiris (Metaphor, 2022)
This study aims to identify code mixing and code switching in Aristarkhov’s Bule KW channel on Bali’s tourism after the Covid-19 pandemic. It also explores the reasons of those code switch and mix. It employs a descriptive qualitative method. Watching and writing are the steps taken in collecting the data, while classifying and interpreting are used in data analysis. The result shows that intra sentential code mix are the most frequently appear. It is followed by intra lexical and changes of pronunciation. Meanwhile the switch is dominated by metaphorical code switch. The reasons involve among other topic changes, quoting others, being emphatic, and expressing group identity.